HEPARIN-BASED NANOPARTICLES: A SUMMARY OF THEIR USES - B. Deepan Kumar, Dr. M. Balaraju, J. Sai Chandra, Syed Safiullah Ghori, Nawaz Mohammed Khan, Md Shoukhatulla Ansari, K.A. Emmanuel, K.V.L.N Murthy, (Chelonian Research Foundation, 2023)
For every review it always shows the deals with nanoparticles for and to be synthesized using heparin and dependent nanoparticles. Such nanoparticles have been widely studied since a long time ago, obtaining satisfactory outcomes. An expressive visually shows these nanoparticles with excellent good comparative characteristics, and since heparin is produced in the human body within the mast cells, this makes these nanoparticles useful for future applications like imaging, disease and cancer treatment, and antibacterial activity. They can also be used for applications that are not oriented directly to the medical and biological areas such as in the case of analyte detection in aqueous solution, although such studies are very few. These nanoparticles synthesis is mainly through wet chemistry methods, using heparin that could have been modified or not. Keywords: Unfractionated Heparin, Nanoparticles, Proteins and Polysaccharides